ACUTE CHOLANGITIS, COMPLICATED BY BILIARY SEPSIS: CLINICAL CASE WITH A FAVORABLE OUTCOME - I. G. Malakhova; A. E. Shklyaev; I. Y. Utkin (Архивъ внутренней медицины)
Now purulent cholangitis has acquired the status of an independent problem on which solution further progress of surgery of a gepatobiliopancreatoduodenal zone depends. Substantially it is caused by increase in number of patients with the complicated cholelithiasis form, especially at elderly people with immunodeficiency and accompanies pathology, tendency to development of a purulent сholangitis and biliary sepsis. The clinical case of the acute purulent cholangitis caused by Klebsiella pneumoniae in the elderly man, and which was complicated by biliary sepsis is presented in article. The surgical decompression of bilious ways in combination with drug therapy (cephalosporin ΙΙΙ generations) was ineffective. The microbiological blood test has helped to specify the activator of septic process, to appoint effective antibacterial therapy that has defined a favorable outcome of a disease at the patient.